CONSUMER TRUST IN MARKETPLACES: A DETERMINING FACTOR IN ONLINE PURCHASING BEHAVIOR - Gunawan Gunawan (Jurnal Ekonomi, 2023)
This study aims to explore in depth how consumer trust is formed toward marketplace platforms and how that trust influences online purchasing behavior. Using a descriptive qualitative approach, data were collected through in-depth interviews with several informants who actively conduct transactions on popular marketplaces in Indonesia. The findings reveal that consumer trust in marketplaces is built through a combination of key factors: transaction security, transparency of product information, quality of service and products, marketplace reputation, and user reviews. Consumers tend to feel more comfortable and confident in making purchases when they are assured of personal data security, receive clear information, and experience good service from the marketplace. These factors significantly influence online purchasing decisions, proving that building trust is a crucial key to enhancing consumer loyalty and satisfaction in e-commerce platforms.